(untitled) (Docentes 2.0 Journal, 2022)
The technology and research relationship is considerable at the time of presenting results, where scientific popularization magazines have the sole purpose of transmitting information to the community in general, where each research expert can capture the results of their studies considering the policies of each dissemination platform. From this perspective, the objective of this work was to know how the Padlet tool influences the dissemination of results generated from the training practice carried out in university training. The methodology used in this study was based on the inductive-deductive method, pragmatic paradigm, hybrid approach, sequential explanatory design, and sequential type. Where 96 university students participated who attended the ordinary academic period 2021, to whom a Likert scale-based survey was applied as an instrument, in addition to direct observation and bibliographic review. The results, elaboration, and dissemination of approximately 40 academic works will be observed, presented from the Padlet tool, and used to disseminate results. In conclusion, the means of disseminating research work are essential today to direct the dissemination of academic writing to optimize the education process at various educational institutions.